Newspaper Wars : Civil Rights and White Resistance in South Carolina, 1935-1965 - Bedingfield, Sid (Book collections on Project MUSE., 2017)
Against all odds, the seeds of social change found purchase in mid-twentieth century South Carolina. Newspaperman John McCray and his allies at the Lighthouse and Informer challenged readers to "rebel and fight"--to reject the "slavery of thought and action" and become "progressive fighters" for equality. Newspaper Wars traces the role journalism played in the fight for civil rights in South Carolina from the 1930s through the 1960s. Moving the press to the center of the political action, Sid Bedingfield tells the stories of the long-overlooked men and women on the front lines of a revolution. African American progress sparked a battle to shape South Carolina's civic life, with civil rights activists arrayed against white journalists determined to preserve segregation through massive resistance. As that strategy failed, white newspapers turned to overt political action and crafted the still-prevalent narratives that aligned southern whites with the national conservative movement. A fascinating portrait of a defining time, Newspaper Wars analyzes the role journalism played--and still can play--during times of social, cultural, and political change. -- Amazon.com.